A mid-Cretaceous petroleum source-rock in the North Atlantic region? Implications of the Nanok-1 fully cored borehole, Hold with Hope, northeast Greenland. (July 2020) - Bojesen-Koefoed, Jørgen A.; Alsen, Peter; Bjerager, Morten; Hovikoski, Jussi; Ineson, Jon; Nytoft, H. Peter; Nøhr-Hansen, Henrik; Petersen, Henrik Ingermann; Pilgaard, Anders; Vosgerau, Henrik
Abstract: The Cenomanian–Turonian transition includes the youngest of the two so-called Cretaceous Oceanic Anoxic Events, sometimes also referred to as the "Bonarelli Event". This is an interval of global deposition of organic-rich oceanic deposits, including some of the most prolific petroleum source rocks of the World. However, in the greater North Atlantic realm, little direct evidence of notable volumes of rich Cenomanian–Turonian petroleum source rocks exists. As part of a major study of the Cretaceous succession in northeast Greenland between 2009 and 2012, a fully cored borehole (Nanok-1) on eastern Hold with Hope was drilled to penetrate a poorly or non-exposed stratigraphic succession including the Cenomanian–Turonian transition. The Nanok-1 penetrated 160.5 m of Cenomanian to Campanian clastic deposits and terminated at a TD of 168.35 m in an igneous intrusion. Although none of the deposits penetrated qualify as a petroleum source rock, a downwards increasing trend in petroleum source potential starting at c. 100m hint at the existence of such rocks at levels deeper than the TD of the well. The downwards increasing trend in petroleum generation potential is curtailed by maturation from c. 140m, but assuming the trend would have prevailed, were it not for the intrusion, the presence of at least a marginal source rock would be expected at the level of the sill and deeper. The presumed existence of petroleum source rocks below the TD of the borehole is supported by the presence of marked oil staining in sandstones (i.e. migrated petroleum) at shallower levels of the drilled succession. The hopane and sterane distributions and stable carbon isotopic compositions and age-specific nordiacholestane ratios of the oil stains are compatible with an origin from the Cretaceous succession, while the Jurassic can be ruled out. The oil stains recorded were probably generated from a marine shale source rock of Cretaceous age, containing a significant proportion of terrigenous organic matter. The possible presence of at least one marginal petroleum source rock in the mid-Cretaceous succession at the Nanok-1 location has implications for the exploration potential of the conjugate margin. Hence, comparison of sediment accumulation histories of the Møre and Vøring basins and northeast Greenland suggests that the presumed source rock was deposited before the accommodation space at the Nanok-1 location was exhausted. Thus, coeval sediment starvation and deposition of more condensed and richer petroleum source rocks may have prevailed in the offshore basins to the east during the mid-late Cenomanian. This potential source rock will thus be slightly older than Cenomanian–Turonian source rocks that are important worldwide. Highlights: The Nanok-1 fully cored borehole, Hold with Hope, NE Greenland, penetrated c.160m of Cenomanian–Campanian deposits and terminated in an intrusion. The borehole did not encounter any petroleum source rocks, but prominent oil stains were found in sandstones drilled by the well. . The oil stains were generated from a Cretaceous-age marine shale source rock. The oil stains document the existence of a Cretaceous-age source rock with capacity for generation of liquid petroleum. The results are important for the ongoing discussion of potential Cretaceous petroleum source rocks in the North Atlantic region.